2022
DOI: 10.3389/fimmu.2022.871769
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Intra-Tumoral Changes Following Immune Checkpoint Blockades in Intrahepatic Cholangiocarcinoma via Single-Cell Analysis

Abstract: PurposeTo dissect the tumor ecosystem following immune checkpoint blockades (ICBs) in intrahepatic cholangiocarcinoma (ICC) at a single-cell level.MethodsSingle-cell RNA sequencing (scRNA-seq) data of 10 ICC patients for the ICB clinical trial were extracted from GSE125449 and systematically reanalyzed. Bulk RNA-seq data of 255 ICC patients were analyzed. Infiltration levels of SPP1+CD68+ tumor-associated macrophages (TAMs) were examined by dual immunofluorescence (IF) staining in 264 resected ICC samples. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…8a ). The strong enrichment of monocytes in PBMC samples and Kupffer cells in Normal phenotype was consistent with physiological distributions of myeloid cells whereas the pro-fibrogenic macrophage Mp_02_SPP1 in ICC and conventional DC featuring LAMP3 expression (DC_CCL19) exhibited significant concentration in ICC and HCC respectively as frequently discussed in literature 26 , 40 , 41 (Fig. 8a ).…”
Section: Technical Validationsupporting
confidence: 83%
“…8a ). The strong enrichment of monocytes in PBMC samples and Kupffer cells in Normal phenotype was consistent with physiological distributions of myeloid cells whereas the pro-fibrogenic macrophage Mp_02_SPP1 in ICC and conventional DC featuring LAMP3 expression (DC_CCL19) exhibited significant concentration in ICC and HCC respectively as frequently discussed in literature 26 , 40 , 41 (Fig. 8a ).…”
Section: Technical Validationsupporting
confidence: 83%
“… 46 The immune fluorescence staining of 264 patients with ICC revealed that high infiltration of SPP1+TAMs was associated with inferior outcomes, consistent with our result. 47 SPP+1 TAMs were reported to interact with FAP+fibroblast cells, remodeling the extracellular matrix and inhibiting the infiltration of immune cells, leading to immunotherapy resistance. 48 Another study in colorectal liver metastasis revealed that patients who respond to neoadjuvant chemotherapy showed a decrease of SPP1+macrophages, while the opposite results were observed in the nonresponders.…”
Section: Discussionmentioning
confidence: 99%
“…The single-cell RNA data included in this study were obtained based on a previous HCC study (GSE125449). 25 …”
Section: Methodsmentioning
confidence: 99%